1078 AUDIT TO IMPROVE APPLICATION OF THE MENTAL CAPACITY ACT ON GERIATRIC WARDS. (14th June 2022) - Chan, J; Mifsud, R W; Ashton, C; Shah, K
Abstract: Introduction: The Mental Capacity Act 2005 (MCA) and Deprivation of Liberty Safeguards (DoLS) are put in place to protect the rights of capacitous patients to make decisions, and in those not deemed to have capacity, the latter ensures that any restrictions are in the patient's best interests, are appropriate and proportionate. The objective of this audit was to assess whether these tools were being appropriately employed across the four Complex Medical Units (CMU) in the John Radcliffe Hospital, in a patient population in which dementia and delirium are prevalent. Method: Audit of patient records on CMU wards (first cycle on 15/8/21 n = 74, second cycle on 31/10/21 (n = 74) before and after presentation of the initial audit results. All inpatients were assessed for: AMTS, completion of a MCA (for those with AMTS<8, or an AMTS not done as too unwell), DoLs applications if indicated. Across the wards, baseline patient characteristics and demographics were equal. In the first audit, there were only 16% patients (6) with an MCA out of a possible 38 patients who fulfilled the criteria and out of these, and 2 had a DOLS (5%). After training, involving a presentation given by us about the findings of our audit, together with high level discussions between consultants and registrars, there were 43% patients with an MCA (15 patients), and 14% had appropriate DOLS (5 patients), out of 35 patients. This therefore shows clear improvement in the situation on our wards. Conclusion: This audit has improved the recognition of patients in whom a capacity assessment is required and the documentation of a MCA being done. Going forward, we suggest all geriatric medicine wards should discuss and audit MCA and DOLS to ensure patients' rights are suitably protected.